2021
DOI: 10.1016/j.msard.2021.102915
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Risk of Relapse in Multiple Sclerosis Patients: A Fight with No Bystander Effect?

Abstract: Background: COVID-19 is speculated to increase the likelihood of relapsing-remitting multiple sclerosis (RRMS) exacerbation. Objective: To investigate the association between contraction of COVID-19 and incidence of acute MS attacks in RRMS patients six months post-infection. Methods: This retrospective cohort study compares the risk of relapse in RRMS patients with (n=56) and without COVID-19 (n=69). Incidence of relapse was recorded for six-month following contraction of COVID-19. Incidence of RRMS exacerbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
1
31
2
Order By: Relevance
“…A better physician-family relationship may also favour the early initiation of treatment, in order to reduce the relapse rate. Interestingly, the control of relapses may acquire further importance in the COVID-19 pandemic era, in light of the speculation (to date disconfirmed) of a higher risk of exacerbation following contraction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A better physician-family relationship may also favour the early initiation of treatment, in order to reduce the relapse rate. Interestingly, the control of relapses may acquire further importance in the COVID-19 pandemic era, in light of the speculation (to date disconfirmed) of a higher risk of exacerbation following contraction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pwMS receiving DMTs are less likely to develop new MS symptom during COVID-19 compared to untreated patients ( 152 ). On the other hand, a possible “protective” effect of COVID-19 on relapse rate was suggested by Etemadifar and colleagues ( 153 ), who conducted a retrospective study on 125 relapsing-remitting pwMS, 56 of whom had laboratory confirmed SARS-CoV-2 infection. Only 7.14% of pwMS in the COVID-19 group experienced a clinical relapse compared with 26.09% of the non-COVID-19 group.…”
Section: Covid-19 and Sars-cov-2 Vaccines In People With Multiple Sclerosis: What We Knowmentioning
confidence: 99%
“…Early reports suggested that individuals with multiple sclerosis (MS) had an increased risk for a worse outcome after contracting COVID-19, based on certain disease characteristics and treatments [ 2 4 ] while other studies disputed these claims [ 5 7 ]. A recent study suggested no significant effects on MS relapse rates after COVID-19 infection [ 8 ]. Nonetheless, it is well recognized that in people without previous neurologic diseases, COVID-19 infection can cause a wide range of neurological complications affecting both the central and peripheral nervous system [ 9 17 ], including cases of new onset demyelinating disease or MS following COVID-19 infection [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%